IMPLEMENTASI KURIKULUM TERPADU SISTEM FULL DAY SCHOOL (Studi Kasus di Madrasah Ibtidaiyah Ibnu Atha’illah Kandangan) - Bahran Bahran (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This study aims to explore information about the model and implementation of the integrated curriculum of the full day school system. This type of research is a descriptive field research using a qualitative approach, taking the background at MI Ibnu Atha'illah Kandangan. The results of the study indicate that the implementation of an integrated curriculum at MI Ibnu Atha'illah: a) planning includes the preparation of a curriculum structure based on the vision and mission of the madrasa, the division of learning time that adopts the boarding school system, and the manufacture of learning tools by teachers taken from various literatures. b) The implementation of learning in the teacher's class uses a variety of methods, but the learning facilities and media are still incomplete, and the priority of teacher qualifications is religious knowledge and the Koran. c) Evaluation of curriculum content is carried out by each teacher in the class, and evaluation of learning outcomes uses written, oral (memorization) and practical test techniques.